2018
DOI: 10.18502/kls.v4i2.1660
|View full text |Cite
|
Sign up to set email alerts
|

Development of Green-Affective Work System for Food SMEs

Abstract: Work system of food Small and Medium-sized Enterprises (SMEs) is influenced by various factors as worker performance, characteristics of raw material, value-added process and workplace environmental ergonomics. Green-affective design analyzes properties of work systems and how these technical attributes could be sensible to the environment (Green) and worker (Affective). The research objectives were: 1) To explore the relationship between green and affective parameters in work systems of Food SMEs; 2) To desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, laborers needed sufficient rest periods under these circumstances. SMEs' work system was influenced by various factors and mainly by workplace environmental ergonomics (Ushada and Okayama, 2018). Determining the rest period could be adapted to reduce ergonomic risk at work (Tiacci, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, laborers needed sufficient rest periods under these circumstances. SMEs' work system was influenced by various factors and mainly by workplace environmental ergonomics (Ushada and Okayama, 2018). Determining the rest period could be adapted to reduce ergonomic risk at work (Tiacci, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ushada et al have developed the modelling of affective temperature control using Artificial Neural Network (ANN) (Ushada et al 2017b). Based on this modelling, hardware of Kansei Engineering-based Sensor for Agro-industry (KESAN) has designed to control environmental ergonomics (Ushada et al 2016). This sensor of KESAN completed the previous development of digital ergonomics to assess integrated workload (Ushada et al 2016) and (Ushada et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…Based on this modelling, hardware of Kansei Engineering-based Sensor for Agro-industry (KESAN) has designed to control environmental ergonomics (Ushada et al 2016). This sensor of KESAN completed the previous development of digital ergonomics to assess integrated workload (Ushada et al 2016) and (Ushada et al 2017c). Ushada also concluded that digital ergonomic is expected to integrate the data of workload, supporting equipment, and environmental ergonomic for the sustainability of SMEs (Ushada 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations